2020
DOI: 10.1080/20008198.2020.1724416
|View full text |Cite
|
Sign up to set email alerts
|

Secondary traumatisation, burn-out and functional impairment: findings from a study of Danish child protection workers

Abstract: Background: Child-protection workers are at elevated risk for secondary traumatization. However, research in the area of secondary traumatization has been hampered by two major obstacles: the use of measures that have unclear or inadequate psychometric properties and equivocal findings on the degree of associated functional impairment. Objective: To assess the relationship between secondary traumatization and burnout using exploratory structural equation modelling (ESEM) and to assess the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
(49 reference statements)
3
7
0
Order By: Relevance
“…CFI = .849, TLI = .834, RMSEA (90% confidence interval [CI]) = .059 [.055, .063], SRMR = .063. Previous research has demonstrated that secondary traumatization and burnout can be modeled as separate constructs and however, also that several cross-loadings between items measuring secondary traumatization and burnout exist and that a CFA model assuming zero cross-factor loadings therefore may be too restrictive when modeling the constructs statistically (Louison Vang et al, 2020). Modification indices indeed suggested that including cross-factor loadings in the model could substantially improve model fit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CFI = .849, TLI = .834, RMSEA (90% confidence interval [CI]) = .059 [.055, .063], SRMR = .063. Previous research has demonstrated that secondary traumatization and burnout can be modeled as separate constructs and however, also that several cross-loadings between items measuring secondary traumatization and burnout exist and that a CFA model assuming zero cross-factor loadings therefore may be too restrictive when modeling the constructs statistically (Louison Vang et al, 2020). Modification indices indeed suggested that including cross-factor loadings in the model could substantially improve model fit.…”
Section: Resultsmentioning
confidence: 99%
“…Modification indices indeed suggested that including cross-factor loadings in the model could substantially improve model fit. A total of eight cross-factor loadings were therefore included in the model, seven based on the size of the modification index (>10) and whether previous research has supported the cross-factor loading (Louison Vang et al, 2020), and one correlated error displaying the highest modification index. The fit statistics of the final measurement model ranged from acceptable to excellent, χ 2 (288) = 713.71, p < .001, CFI = .909, TLI = .898, RMSEA [90% CI] = .047 [.042, .051], SRMR = .047, and is displayed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This measure has been known across mental health professionals since its conception in 1995 (ProQOL: Professional Quality of Life, 2021) and is commonly used to measure constructs such as compassion fatigue, secondary trauma, and burnout. Similar to all good measures, the ProQOL has been extensively critiqued; recent scholars evaluating the measure call into question its construct and discriminant validity (Geoffrion et al, 2019; Stamm et al, 2012; Vang et al, 2020). Nevertheless, its continued utility across multiple disciplines remains patent in extant research (Buselli et al, 2020; Van Kirk, 2021; Wolf et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a Danish child protection workers survey (N = 667) which investigated the relationship between STS, BO and job satisfaction concluded that both STS and BO were unrelated to job satisfaction (Louison Vang et al, 2020 ). Some studies have previously noted that high levels of emotional exhaustion do not impact the level of job satisfaction among a population of child protection workers, which might be explained by the buffering effect of organizational factors, such as job resources and support (Stalker et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%